Mechanical Engineering Needs to Pursue Excellence - Thareja, Priyavrat (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
That ‘Mechanical Engineering must Pursue Excellence’ is not a new need. But in the light of new disruption, Current Technological Revolution (CTR) imbibed by newer intelligence, Integration of Technologies, including that of the information and communication technology advancements, including that of materials; which all demand a better understanding of the newer challenges further challenge Mechanical Engineers’ competencies. How to cite this editorial: Thareja P. Mechanical Engineering Needs to Pursue Excellence. J Adv Res Mech Engi Tech 2019; 6(1&2): 1-3.